Nyangku Traditional Ceremony: How Does the Community Effort to Preserve It and What is the Impact on Social Learning and Students' Curious Character? - Andri Priyanto; Tan Joo Siang; Thi Mai Lan Nguyen (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research is intended to determine the efforts made by the Panjalu community in preserving the Nyangku Traditional Ceremony and the participation of the Panjalu community in preserving the Nyangku Traditional Ceremony. Methodology: This research is qualitative research with a phenomenological approach. The population in this study were all communities involved in the Nyangku traditional ceremony. The data collection technique is interviews with community leaders, traditional leaders and traditional members. Data analysis uses a qualitative approach to identify patterns, themes and meanings that emerge from participant narratives. Main Findings: The results of the research show that there have been changes in the Nyangku Traditional Ceremony, namely way of dressing which is starting to have modern elements, the opening ceremony which begins with entertainment events and night market, well collaboration with the government level. Community participationefforts to preserve the ceremony includes financial participation the form of assistance from the government and alms from community, participatio property and from pre-implementation to completion, participation in skills by displaying various types of art. Novelty/Originality of this study: This research presents innovation by revealing how the Nyangku traditional ceremony in Panjalu District, Ciamis, West Java, can be contextually integrated into the social learning curriculum, creating a comprehensive learning experience and stimulating students' curiosity about local values and their history. Through this approach, this research presents a new perspective in utilizing local wisdom as a dynamic learning resource and contributes to the development of students' curious character in the context of formal education.